Data on conceptual design and simulation of reactive distillation process - Mallaiah Mekala (Data in Brief, 2019)
The simulation of the reactive distillation for the esterification of acetic acid with methanol is carried out using the equilibrium stage model. The pseudo-homogeneous kinetic rate equation is used in equilibrium stage model to perform simulation in Aspen plus Version 7.3. The different parameters like the reflux ratio, number of stages, feed location of the acetic acid are used to obtain the data of mixture composition and acetic acid conversion. The non-ideal behavior of the system is accounted by NRTL, Wilson and UNIQUAC methods. All the thermodynamic models are able to generate data of compositions very well. The composition profiles with different activity based models compared and there is little deviation of water and methanol mole fractions. The optimum number of stages for the present system is 30 for achieving the higher conversion as well as the purity of the distillate. The optimum reflux ratio is 1.9, feed flow rate of acetic acid and methanol is 10.2 mol/hr, location of acetic acid above the reactive zone and methanol below the reactive zone gives the 99.5% by mole of the methyl acetate and 99% acetic acid conversion. Keywords: Esterification, Kinetic model, Aspen plus, Simulation, Stage number, Conversion